Adsorptive Performance of Polypyrrole-Based KOH-Activated Carbon for the Cationic Dye Crystal Violet: Kinetic and Equilibrium Studies. (20th March 2021) - Alghamdi, Abdulaziz Ali; Al-Odayni, Abdel-Basit; Abduh, Naaser A. Y.; Alramadhan, Safiah A.; Aljboar, Mashael T.; Saeed, Waseem Sharaf
Abstract : The aim of this work was to investigate the adsorptive performance of the polypyrrole-based KOH-activated carbon (PACK) in the removal of the basic dye crystal violet (CV) using a batch adsorption system. The equilibrium data, obtained at different initial CV concentrations (C 0 = 50 – 500 mg / L ) and temperatures (25–45°C), were interpreted using the Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich isotherms, with the Langmuir model providing a better fit (R 2 ≥ 0.9997 ) and a maximum adsorption capacity of 497.51 mg/g at 45°C. Under the examined conditions, the values of the thermodynamic parameters free energy, enthalpy, and entropy indicate a spontaneous, endothermic, and physisorption adsorption process. The kinetic data of the adsorption process were very well described by a pseudo-second-order model (R 2 ≥ 0.9996 ). However, surface diffusion seems to be the main rate-controlling step. Thus, we concluded that PACK shows commercial potential for the removal of cationic dyes such as CV from industrial effluent.